2015
DOI: 10.1158/1535-7163.mct-14-0969
|View full text |Cite
|
Sign up to set email alerts
|

Blocking IL1β Pathway Following Paclitaxel Chemotherapy Slightly Inhibits Primary Tumor Growth but Promotes Spontaneous Metastasis

Abstract: Acquired resistance to therapy is a major obstacle in clinical oncology, and little is known about the contributing mechanisms of the host response to therapy. Here, we show that the proinflammatory cytokine IL1b is overexpressed in response to paclitaxel chemotherapy in macrophages, subsequently promoting the invasive properties of malignant cells. In accordance, blocking IL1b, or its receptor, using either genetic or pharmacologic approach, results in slight retardation of primary tumor growth; however, it a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 31 publications
7
50
0
Order By: Relevance
“…Both mouse and human Endothelin 1 mRNA levels was decreased 2 fold and 2.8 fold respectively following administration of anakinra via the treatment or preventative protocols compared with placebo (P < 0.01; Figure 2e). Repeated administration of a higher dose of anakinra, 10mg/kg, have previously been shown to increase macrophage infiltration into tumours [24]. In our current study 1mg/kg/day anakinra did not affect macrophage infiltration into tumours within bone (Figure 2f).…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Both mouse and human Endothelin 1 mRNA levels was decreased 2 fold and 2.8 fold respectively following administration of anakinra via the treatment or preventative protocols compared with placebo (P < 0.01; Figure 2e). Repeated administration of a higher dose of anakinra, 10mg/kg, have previously been shown to increase macrophage infiltration into tumours [24]. In our current study 1mg/kg/day anakinra did not affect macrophage infiltration into tumours within bone (Figure 2f).…”
Section: Resultssupporting
confidence: 53%
“…Our data suggest that these anti-tumour effects are a result of changes in the tumour microenvironment, as direct incubation of MDA-MB-231-IV cells with anakinra did not exert anti-tumour affects in vitro (Supplementary Figure S1). The bone is rich in remodelling cytokines, including TNF alpha, IL-1B and IL-6, and previous studies have reported that incubation of MDA-MB-231 cells with a combination of these cytokines in a 3D model system stimulates their proliferation [24]. In our study, administration of anakinra significantly reduced expression of TNF alpha and IL-1B in bone (Figure 3) and reduced levels of these molecules is likely to have contributed to the anti-tumour effects observed.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that following PTX therapy, the balance between M1 and M2 macrophages is disrupted in tumors. The blockade of interleukin 1β (IL-1β) in PTX-treated mice results in an increased number of infiltrating M2 macrophages in tumors, leading to increased metastasis (Voloshin et al., 2015). Thus, the specific macrophage state that contributes to tumor lymphangiogenesis following PTX therapy remains to be established.…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow transplantation was performed as previously described (Voloshin et al., 2015). Details are provided in Supplemental Experimental Procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, dual effects of blocking the IL1 pathway on tumor growth are possible. Therefore, treatments using “add-on” drugs such as the IL-1β blocker to conventional chemotherapy should be investigated in appropriate tumor models monitoring both the primary tumor and the induction of metastases [278]. …”
Section: Anti-cancer Agents Induce Il-1βmentioning
confidence: 99%